Advancing functional foods: a systematic analysis of plant-derived exosome-like nanoparticles and their health-promoting properties - Che, Ke; Wang, Cong; Chen, Hao (Frontiers in Nutrition, 2025)
Plant-derived exosome-like nanoparticles (PDENs), emerging as novel bioactive agents, exhibit significant potential in food science and nutritional health. These nanoparticles, enriched with plant-specific biomolecules such as proteins, lipids, nucleic acids, and secondary metabolites, demonstrate unique cross-species regulatory capabilities, enabling interactions with mammalian cells and gut microbiota. PDENs enhance nutrient bioavailability by protecting sensitive compounds during digestion, modulate metabolic pathways through miRNA-mediated gene regulation, and exhibit anti-inflammatory and antioxidant properties. For instance, grape-derived PDENs reduce plasma triglycerides in high-fat diets, while ginger-derived nanoparticles alleviate colitis by downregulating pro-inflammatory cytokines. Additionally, PDENs serve as natural drug carriers, with applications in delivering therapeutic agents like doxorubicin and paclitaxel. Despite these advancements, challenges remain in standardizing extraction methods (ultracentrifugation, immunoaffinity), ensuring stability during food processing and storage, and evaluating long-term safety. Current research highlights the need for optimizing lyophilization techniques and understanding interactions between PDENs and food matrices. Furthermore, while PDENs show promise in functional food development—such as fortified beverages and probiotic formulations—their clinical translation requires rigorous pharmacokinetic studies and regulatory clarity. This review synthesizes existing knowledge on PDENs’ composition, biological activities, and applications, while identifying gaps in scalability, stability, and safety assessments. Future directions emphasize interdisciplinary collaboration to harness PDENs’ potential in combating metabolic disorders, enhancing food functionality, and advancing personalized nutrition strategies.